2018
DOI: 10.1098/rspb.2017.2754
|View full text |Cite|
|
Sign up to set email alerts
|

Trait evolution, resource specialization and vulnerability to plant extinctions among Antillean hummingbirds

Abstract: Species traits are thought to predict feeding specialization and the vulnerability of a species to extinctions of interaction partners, but the context in which a species evolved and currently inhabits may also matter. Notably, the predictive power of traits may require that traits evolved to fit interaction partners. Furthermore, local abiotic and biotic conditions may be important. On islands, for instance, specialized and vulnerable species are predicted to be found mainly in mountains, whereas species in l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(64 citation statements)
references
References 60 publications
(100 reference statements)
3
60
0
1
Order By: Relevance
“…This result is consistent with the expected reduction in interspecific competition in unproductive environments at high elevations (Ebeling et al, ; Fründ et al, ; MacArthur & Pianka, ), which may lead to niche expansion of pollinator species (Hoiss et al, ; Miller‐Struttmann & Galen, ). The findings are also congruent with previous research in other pollinator taxa, such as hummingbirds, which have been found to be more generalist at high elevations because of both food niche expansion and environmental filtering (Maglianesi et al, ; but see Dalsgaard et al, for contrasting results). Still, another key result was that the most common pollinators groups, dipterans and hymenopterans, showed a larger body size but also trait clustering (lower FDis) at higher elevation, and trait overdispersion (larger FDis) at lower elevation.…”
Section: Discussionsupporting
confidence: 91%
“…This result is consistent with the expected reduction in interspecific competition in unproductive environments at high elevations (Ebeling et al, ; Fründ et al, ; MacArthur & Pianka, ), which may lead to niche expansion of pollinator species (Hoiss et al, ; Miller‐Struttmann & Galen, ). The findings are also congruent with previous research in other pollinator taxa, such as hummingbirds, which have been found to be more generalist at high elevations because of both food niche expansion and environmental filtering (Maglianesi et al, ; but see Dalsgaard et al, for contrasting results). Still, another key result was that the most common pollinators groups, dipterans and hymenopterans, showed a larger body size but also trait clustering (lower FDis) at higher elevation, and trait overdispersion (larger FDis) at lower elevation.…”
Section: Discussionsupporting
confidence: 91%
“…However, it corresponds to a recent finding that niche partitioning (i.e. specialization) in insular Caribbean plant–hummingbird networks is determined by topographical and climatic conditions rather than by hummingbird traits (Dalsgaard et al., ). Thus, it is likely that traits have a stronger role in structuring hummingbird–plant interactions within local communities/networks rather than in cross‐biomes and island systems (Dalsgaard et al., ).…”
Section: Discussionsupporting
confidence: 88%
“…specialization) in insular Caribbean plant–hummingbird networks is determined by topographical and climatic conditions rather than by hummingbird traits (Dalsgaard et al., ). Thus, it is likely that traits have a stronger role in structuring hummingbird–plant interactions within local communities/networks rather than in cross‐biomes and island systems (Dalsgaard et al., ). Especially as species with similar traits are assembled in different modules and thus there is no strong difference on trait distribution across cross‐biomes modules.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns in the specialization of plant–insect pollinator interactions have been reported from biogeographically independent regions, including the Alps (Hoiss et al, , network level), Colorado Rocky Mountains (Miller‐Struttmann & Galen, , intraspecific and network level), the Andes (Ramos‐Jiliberto et al, , network level), and an island volcano in Tenerife, Canary Islands (Lara‐Romero et al, , network and community level). Far less consistent are the patterns reported from plant–hummingbird interactions along elevational gradients, which were either more generalized in the highlands (Maglianesi, Blüthgen, Böhning‐Gaese, & Schleuning, ), or in the lowlands (Dalsgaard et al, ). Similarly contradicting are the results from meta‐analyses describing specialization patterns along other temperature gradients, that is, latitudinal gradients.…”
Section: Discussionmentioning
confidence: 97%
“…We showed that Hymenoptera were on average more specialized than Diptera, which is in agreement with reports from the literature (Benadi et al, ; Weiner, Werner, Linsenmair, & Blüthgen, ) and which can be explained by the fact that bee larval survival depends on the pollen source (Praz et al, ). Morphological traits were not related to the degree of species specialization, indicating that traits of one trophic level are not informative to predict specialization (Dalsgaard et al, ). Trait matching between trophic levels, in contrast, can sharpen our understanding about how species traits structure species interactions and network architecture (Albrecht et al, ; Bender et al, ; Dehling et al, ).…”
Section: Discussionmentioning
confidence: 99%